Expanding the Availability of Scalp Cooling to All Patients at Risk of Chemotherapy-Induced Alopecia - Portia Lagmay-Fuentes; Andrea Smith; Shannon Krus; Laurie Lewis; Asma Latif; Tiffany Gagliardo; Manpreet Kohli (Taylor & Francis Group, 2024)
Alopecia is an undesirable side effect of cancer chemotherapy. The mitigation of alopecia is a desirable adjunct treatment for patients with cancer. FDA-cleared scalp cooling (SC) devices have been successfully used to prevent or reduce chemotherapy-induced alopecia (CIA). This paper provides an understanding of the implementation and value of the new Insurance-Based Billing Model used in the USA for SC and its benefits compared with the original self-pay model. This improved compensation change will result in all patients in need, including underserved and disadvantaged populations, receiving equitable healthcare by allowing access to this valuable supportive care technology.